Improving knowledge on child abandonment and care in Africa : a demographic contribution to the achievement of child protection - (:unkn) unknown (My University, 2011)
Carrying out a focused literature review on child abandonment and care in Africa, this paper aims to show that the understanding of this question remains very incomplete, the classification of situations is unsettled and their measurement is lacking in terms of both prevalence and trends. Argumentation is founded on a conceptual framework that gives a central place to the concept of disruption in the process of childcare, and that suggests determinant factors causing disruption and possible responses from families or from institutions. Some socio-cultural and economic factors highlight disruptions in the process of child care. Responses to these disruptions are largely familial, but also institutional. Some circumstances can lead to abandonment or child endangerment. The anthropology of infancy gives a great deal of information on cultural and social foundations of abandonment and on family systems of child circulation. Child demography remains focused on mortality, nutrition, education and birth registration. Demographic analyses give few answers on disruption in child care. It appears important today to improve data collection in order to better understand 1) child status in the family and mechanisms of solidarity that involve children; 2) issues concerning street children and working children; 3) situation of child endangerment outside as well as inside the family. Thus, progress of social science research, particularly in demography, on these issues in Africa would give important results necessary for improving policies regarding child protection. Résumé S'appuyant sur une revue de la littérature sur l'abandon et la prise en charge des enfants en Afrique, cet article vise à montrer que cette problématique n'est pas explorée en profondeur, que la diversité des situations est mal connue et que les mesures font défaut, tant en terme de prévalence que de tendance. L'argumenta-tion se base sur un cadre conceptuel qui accorde une place centrale
Keywords: African Research